2013
DOI: 10.3917/polaf.131.0027
|View full text |Cite
|
Sign up to set email alerts
|

« Entrepreneurs de la frontière » : le rôle des comptoirs privés dans les sites d'extraction artisanale de l'or au Burkina Faso

Abstract: Au Burkina Faso, le secteur aurifère est en plein essor et les sites d’extraction artisanale en sont une composante importante. Si l’exploitation artisanale échappe en large partie aux tentatives de contrôle par la législation formelle, des formes variées de gouvernance réelle se mettent en place pour assurer la régulation de la vie et du travail dans les sites d’orpaillage. Dans le cas présenté ici, un rôle central est assumé par les représentants locaux d’une société privée de commercialisation de l’or, « en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…This is a polysemic term, designating not only the space dedicated to the processing of gold ore but also the local private company controlling all purchases and sales of the mineral produced in the site 2 (cf. Arnaldi di Balme & Lanzano, 2013;Côte & Korf, 2018;Werthmann, 2017). Until the mid-2000s, this was a prerogative of the Comptoir Burkinabè des Métaux Précieux (CBMP), a parastatal body charged with the commercialization of all gold produced nationally.…”
Section: The Social Organization Of Mercury-based Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a polysemic term, designating not only the space dedicated to the processing of gold ore but also the local private company controlling all purchases and sales of the mineral produced in the site 2 (cf. Arnaldi di Balme & Lanzano, 2013;Côte & Korf, 2018;Werthmann, 2017). Until the mid-2000s, this was a prerogative of the Comptoir Burkinabè des Métaux Précieux (CBMP), a parastatal body charged with the commercialization of all gold produced nationally.…”
Section: The Social Organization Of Mercury-based Productionmentioning
confidence: 99%
“…The status of private comptoirs has been somewhat uncertain, and their modes of action often contributed to blur the distinction between formal legal status and informal strategies to establish economic control and secure support from local powerful actors (cf. Arnaldi di Balme & Lanzano, 2013;Côte & Korf, 2018). Adopted in 1997 and then revised in 2003 and 2015, 3 the national mining legislation has identified different categories of permits and authorizations in the artisanal mining sector, covering activities in both extraction/production and commercialization, each with specific limits of validity in time and space.…”
Section: The Social Organization Of Mercury-based Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Managers under this arrangement can sometimes earn monthly incomes as high as USD 9700 [8,47]. In the third system of regulation, authorized companies arranged ("comptoirs" among others) order on the mining camps with either the collaboration of former miners and private security officers [46,49]. Usually, prior to the establishment of the comptoir, the representatives of the comptoir would negotiate with customary authorities and local government officials (mayors, prefects).…”
Section: Artisanal Miningmentioning
confidence: 99%
“…Regarding the work organization in mine pits, literature reported that working teams size is estimated at 30 people or more and that there is an individual known as patron in French who is responsible for covering all work-related expenses, a team leader [3,9,34,41,49,55]. In Zincko and Siguinoguin, between two and 20 people work in each pit.…”
Section: Position Rulesmentioning
confidence: 99%